Knowledge, attitude and management practices of fertilizer and pesticide application among pineapple farmers / Nor Hafiza Rosli - Rosli, Nor Hafiza (Faculty of Plantation and Agrotechnology, 2015)
Pineapple industry is one of main contributor of Malaysia's economy since 1957. The application of fertilizer and pesticide is necessary in improving productivity of agriculture. However, the impacts of excessive chemical were lead to undesirable effects on yield and environment. A case study was carried out in Pontian, Johor, which seeks to identify the relationship between knowledge, attitude, and management practices of fertilizer and pesticide application among pineapple farmers. A total of 121 respondents were involved in the data collection process. The data were gained though distributing questionnaire. The resulting analysis indicated that there is weak positive relationship between fanners' knowledge and attitude of fertilizer and pesticide application (r = .207, P = .023). Farmers' knowledge and management practices of fertilizer and pesticide application also shown a weak positive relationship (r = .274, P = .002). Additionally, there is a strong positive relationship between attitudes and management practices of fertilizer and pesticide application among farmers (r = .657, P = .00). In conclusion, fanners should have adequate knowledge and positive attitudes in term of applying good management practices of fertilizer and pesticide application on cultivated crop